2014
DOI: 10.5664/jcsm.3968
|View full text |Cite
|
Sign up to set email alerts
|

Do Respiratory Cycle-Related EEG Changes or Arousals from Sleep Predict Neurobehavioral Deficits and Response to Adenotonsillectomy in Children?

Abstract: Study Objectives: Pediatric obstructive sleep apnea (OSA) is associated with hyperactive behavior, cognitive defi cits, psychiatric morbidity, and sleepiness, but objective polysomnographic measures of OSA presence or severity among children scheduled for adenotonsillectomy have not explained why. To assess whether sleep fragmentation might explain neurobehavioral outcomes, we prospectively assessed the predictive value of standard arousals and also respiratory cycle-related EEG changes (RCREC), thought to ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Mean number of arousals per hour for the entire cohort reduced from 13.8 to 11.2. This is similar to the 14% decrease reported by Chervin et al [ 60 ] who found no association between sleep fragmentation, defined by respiratory cycle-related changes in the EEG, and neurobehavioral outcomes following treatment. The mixed model analysis used in the current study may have provided the statistical sensitivity to detect an association, however the clinical relevance needs to be considered.…”
Section: Discussionsupporting
confidence: 90%
“…Mean number of arousals per hour for the entire cohort reduced from 13.8 to 11.2. This is similar to the 14% decrease reported by Chervin et al [ 60 ] who found no association between sleep fragmentation, defined by respiratory cycle-related changes in the EEG, and neurobehavioral outcomes following treatment. The mixed model analysis used in the current study may have provided the statistical sensitivity to detect an association, however the clinical relevance needs to be considered.…”
Section: Discussionsupporting
confidence: 90%
“…Primary nocturnal enuresis among children with snoring referred for polysomnography is a significant predictor of OSAS severity (class IV) [106]. However, neither the AHI nor sophisticated measures of sleep fragmentation, such as respiratory cycle-related electroencephalogram (EEG) changes, are associated with behavioural problems, cognitive deficits or sleepiness, and they do not explain the improvement in neurobehavioral outcomes following adenotonsillectomy (meta-analysis, class III and IV) [92,145,149,150]. b) In the CHAT study, participants with moderate-to-severe disease (AHI >4.7 episodes·h −1 ) assigned to watchful waiting were less likely to improve spontaneously compared with those with mild disease (class I) [126].…”
Section: 3mentioning
confidence: 99%
“…Furthermore, obstructive events, and increases in respiratory efforts with or without arousals may not necessarily be reflected by gas exchange alterations or even by visually recognizable EEG arousals. This is restricting the recognition of respiratory‐related sleep fragmentation that has been identified as an important contributor to OSA morbidity 18–21 . Thus, it is highly desirable when adopting innovative techniques for diagnosis of pediatric OSA to include a reliable assessment of respiratory effort (RE).…”
Section: Introductionmentioning
confidence: 99%
“…This is restricting the recognition of respiratoryrelated sleep fragmentation that has been identified as an important contributor to OSA morbidity. [18][19][20][21] Thus, it is highly desirable when adopting innovative techniques for diagnosis of pediatric OSA to include a reliable assessment of respiratory effort (RE). Application of such advanced diagnostic approaches has recently greatly benefited from the advent of machine learning applications in the field of sleep medicine, as those techniques can facilitate complex signal processing and improve reproducibility of sleep staging and respiratory pattern evaluation.…”
mentioning
confidence: 99%